STUDI KASUS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PADA TIKUNGAN TAJAM - Ryan Manggala; Jeffry Angga J.; Djoko Purwanto; Amelia Kusuma Indriastuti (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Hairpin curve is an accident prone location. The number of accidents on curve 1,5 to 4 times much more than on straight road. This study aimed to evaluate the geometric conditions on some curve that is reviewed by applicable geometric rules, to determine the characteristics of the accidents, to determine the relationship of modeling the causes of accidents, to determine the main factors causing traffic accidents, and provide troubleshooting recommendations. The analysis that is carried out are analysis of geometric condition evaluation, accident characteristics analysis, and cross tabulation analysis. Based on the evaluation of the geometric conditions, on all of the third curves there are not reach the technical standards because under minimum curve radius and the value of SMS of sample vehicle variety more than SS curve calculation speed limit nearly reach 50%. Based on the characteristics of accidents, on the third curves showed that the dominant factor causing accidents is human factor (70%). The results of study relationship between curve radius and degree of fatality indicate the value of R Square 0,859, meanwhile relationship between speed and degree of fatality indicate the value of R Square 0,91. The sum of the analysis showed the main factor causing traffic accidents is human factor specificly to the speed factor and then continued by curve radius factor. Several attempts types of treatment that can be applied is to install speed limit signs in some specific locations, make rumble strips before entering the hairpin curves.